-4x+-40-6=-3-6

Simple and best practice solution for -4x+-40-6=-3-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4x+-40-6=-3-6 equation:


Simplifying
-4x + -40 + -6 = -3 + -6

Reorder the terms:
-40 + -6 + -4x = -3 + -6

Combine like terms: -40 + -6 = -46
-46 + -4x = -3 + -6

Combine like terms: -3 + -6 = -9
-46 + -4x = -9

Solving
-46 + -4x = -9

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '46' to each side of the equation.
-46 + 46 + -4x = -9 + 46

Combine like terms: -46 + 46 = 0
0 + -4x = -9 + 46
-4x = -9 + 46

Combine like terms: -9 + 46 = 37
-4x = 37

Divide each side by '-4'.
x = -9.25

Simplifying
x = -9.25

See similar equations:

| 4+4b=4 | | 7n-18+1=19 | | 8.2(s+4)=6.7x+5.2 | | b-2+3b+6=4 | | 6p-1=p+20 | | 6(x+8)=7X+3 | | 27*x=1800 | | 6(X+8)=7x-3 | | -6+3X-3Y=0 | | 0=-Y+X-4 | | -3+2X=Y | | 7x+5x+10= | | y+5=-10(X-1) | | 18x^2-47x-56=0 | | 3+(5a+5)=35 | | -1-9x=9x+19 | | 15*x^10=67 | | 7(4b-1)=-3b-2 | | 3(2m-10)=2m+10 | | 20=14m-9+3(5m) | | 17-x=3x-7 | | 8x-6=-2(6x+4)+2x | | x^5-4x^4+x^3+2=0 | | 47+3=40 | | X=45 | | y=4-xsqaured | | 16y^2+28=0 | | 10x+11y= | | x^4+5x^2+49=0 | | -(-x-5)+5(x-9)=2(x+8)-2x+5 | | 3n+2=9 | | 2x=3(1-x)-(x-1) |

Equations solver categories